1990
DOI: 10.1111/j.1439-0450.1990.tb01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Nachweis des bovinen Herpesvirus Typ 1 (BHV1) mittels Intrakutantest II. Mitteilung: Experimentelle Untersuchungen

Abstract: Summary Investigations concerning the proof of BHV1 infection by an intradermal test II. Experiments A purified concentrated BHV1 antigen that had been tested in field trials was also tested under isolated conditions in BHV1 positive and negative cattle. The antigen proved to act specifically even after storage for 2 years at + 4 °C or for 6 months at 37 °C. The best results were obtained when the test was read 48–72 hours after the injection, which is in agreement with the field trials. The increase in skin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…O u r data are in agreement with those by STRAUB et al (1990) who in experiment performed on 6 seronegative calves and 3 with passively acquired antibodies, found that sixtuple administration of the antigen between 3 and 67 weeks of their life, caused no seroconversion or positive DTH reaction. In a study of DEPTULA (1988) repeated skin testing exerted no effect on the immune status of 25 seronegative cattle.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…O u r data are in agreement with those by STRAUB et al (1990) who in experiment performed on 6 seronegative calves and 3 with passively acquired antibodies, found that sixtuple administration of the antigen between 3 and 67 weeks of their life, caused no seroconversion or positive DTH reaction. In a study of DEPTULA (1988) repeated skin testing exerted no effect on the immune status of 25 seronegative cattle.…”
Section: Discussionsupporting
confidence: 90%
“…A possibility of detecting cattle infected with bovine herpesvirus type 1 (BHV-1) following intradermal injection of inactivated BHV-1 antigen was first demonstrated by DARCEL and DORWARD (1972). Further studies documented a diagnostic value of the intradermal (ID) testing (a delayed-type hypersensitivity test) of cattle infected with BHV-1 STRAUB et al, 1990;WIZIGMANN et al, 1989). Since this test is based on the intradermal administration of the virus antigen, it is essential from a practical point of view to know the effect it exerts on the immune status especially in animals free from BHV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 1983;STRAUB et al, 1990) a high agreement (94.5 YO) was found between the VN24 and ID results. Moreover ID test compared to VN24 one showed also a high specificity and sensitivity.…”
mentioning
confidence: 64%
“…To make the test comparable it is essential to establish a threshold value for the skin positive reactions unequivocally. Such the value was different and rather arbitrary accepted in earlier reports (CORREA-GIR6N et al, 1975;AGUILAR-SETIBN et al, 1983;STRAUB et al, 1990).…”
Section: Introductionmentioning
confidence: 75%
“…Lately an intradermal test has been introduced whereby it is for example possible to differentiate between a passively and an actively acquired immunity [9][10][11].…”
Section: Diagnosismentioning
confidence: 99%